Multiple isoforms of ADAM12 in breast cancer: differential regulation of expression and unique roles in cancer progression - Duhachek Muggy, Sara (Kansas State University, 2014)
The ADAM (A Disintegrin and Metalloprotease) family of multi-domain proteins modulates a number of cellular signaling pathways in both normal and cancerous cells. ADAM12 has been shown to be a candidate cancer gene for breast cancer and its expression is up-regulated in breast tumors. The human ADAM12 transcript is alternatively spliced. One of these splice variants encodes a transmembrane ADAM12 isoform, ADAM12-L, which has been demonstrated to release cell signaling molecules from the cell surface. Another variant encodes a secreted protease, ADAM12-S, which cleaves extracellular matrix proteins and other secreted proteins. Although these variants are expressed from the same promoter, their relative expression levels are highly discordant. Here, I demonstrate variant-specific regulation of ADAM12 transcripts by microRNAs. Members of the microRNA-29 and microRNA-200 families target the unique 3’UTR of the ADAM12-L transcript and cause transcript degradation. Additionally, I show the presence of a novel ADAM12 splicing event in which 9 additional nucleotides are inserted in the region encoding the autoinhibitory pro-domain. I demonstrate that this novel variant is expressed in breast epithelial cells and breast cancer cell lines. The resulting protein isoform does not undergo proteolytic processing to activate the protease. Additionally, trafficking of the novel isoform to the cell surface is impaired and this isoform is localized to the endoplasmic reticulum. Finally, I determined a role for ADAM12-L in the progression of triple negative breast cancers (TNBCs). These tumors are lacking expression of hormone receptors and the HER2 receptor. HER2 is a member of the epidermal growth factor receptor (EGFR) family and the loss of the HER2 receptor causes tumors to rely on EGFR for propagating pro-growth signals. I show here that, in TNBC tumors, ADAM12-L expression is strongly correlated with poor patient prognosis and increased activation of EGFR. These data suggest that in TNBCs, ADAM12-L enhances tumor growth via EGFR activation. Collectively, the data presented here demonstrate (a) transcript-specific regulation of ADAM12 in breast cancer, (b) the existence of a novel splice variant and protein isoform with impaired cellular trafficking, and (c) an important role of the ADAM12-L isoform in EGFR activation in TNBC.
Keywords: ADAM12; Breast cancer; Gene expression; EGFR signaling; Alternative splicing; Triple negative breast cancer; MicroRNA; Biochemistry (0487); Cellular Biology (0379); Molecular Biology (0307)